Water electrolysis with a conducting carbon cloth: subthreshold hydrogen generation and superthreshold carbon quantum dot formation - Biswal, Mandakini; Deshpande, Aparna; Kelkar, Sarika; Ogale, Satishchandra (ChemSusChem, 2014)
A conducting carbon cloth, which has an interesting turbostratic microstructure and functional groups that are distinctly different from other ordered forms of carbon, such as graphite, graphene, and carbon nanotubes, was synthesized by a simple one-step pyrolysis of cellulose fabric. This turbostratic disorder and surface chemical functionalities had interesting consequences for water splitting and hydrogen generation when such a cloth was used as an electrode in the alkaline electrolysis process. Importantly, this work also gives a new twist to carbon-assisted electrolysis. During electrolysis, the active sites in the carbon cloth allow slow oxidation of its surface to transform the surface groups from COH to COOH and so forth at a voltage as low as 0.2V in a two-electrode system, along with platinum as the cathode, instead of 1.23V (plus overpotential), which is required for platinum, steel, or even graphite anodes. The quantity of subthreshold hydrogen evolved was 24mLcm(-2)h(-1) at 1V. Interestingly, at a superthreshold potential (>1.23V+overpotential), another remarkable phenomenon was found. At such voltages, along with the high rate and quantity of hydrogen evolution, rapid exfoliation of the tiny nanoscale (5-7nm) units of carbon quantum dots (CQDs) are found in copious amounts due to an enhanced oxidation rate. These CQDs show bright-blue fluorescence under UV light.
Keywords: Carbon; electrolysis; Hydrogen; photoluminescence; quantum dots

Hybrid perovskite quantum nanostructures synthesized by electrospray antisolvent-solvent extraction and intercalation - Naphade, Rounak; Nagane, Satyawan; Shanker, G. Shiva; Fernandes, Rohan; Kothari, Dushyant; Zhou, Yuanyuan; Padture, Nitin P.; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2016)
Perovskites based on organometal lead halides have attracted great deal of scientific attention recently in the context of solar cells and optoelectronic devices due to their unique and tunable electronic and optical properties. Herein, we show that the use of electrospray technique in conjunction with the antisolventsolvent extraction leads to novel low-dimensional quantum structures (especially 2-D nanosheets) of CH3NH3PbI3- and CH3NH3PbBr3-based layered perovskites with unusual luminescence properties. We also show that the optical bandgaps and emission characteristics of these colloidal nanomaterials can be tuned over a broad range of visible spectral region by compositional tailoring of mixed-halide (I- and Br-based) perovskites.
Keywords: 2D nanostructure systems; antisolvent-solvent extraction; bandgap tuning; electrospray; nanosheets; perovskite; quantum dots